Impact of the physical structure of feed on performance, diet digestibility, and macroscopic anatomical changes in the oropharyngeal cavity of broilers - Dias, Isabella de Camargo; Izabel Vieira, Vivian; Britto Doi, Ana Carolina; de Paes de Melo Neta, Suzete; Luís Krabbe, Everton; Maiorka, Alex (Archives of Veterinary Science, 2025)
The study evaluated the impact of different pellet ratios on performance, diet digestibility, and changes in the oropharyngeal cavity in broiler chickens. One hundred sixty male broilers, aged 28 to 42 days, were distributed in a completely randomized design with four treatments and eight replicates of five birds each. These were M100 (control diet; 100% mash), P34 (34% pelleted), P66 (66% pelleted), and P100 (100% pelleted). At 28, 35, and 42 days of age, body weight gain (BWG), feed intake (FI), and feed conversion ratio (FCR) were assessed. At 42 days of age, ileal digesta was collected from two birds per repetition to determine the apparent ileal digestibility (AID) of dry matter (DM), crude protein (CP), and ileal digestible energy (IDE). In addition, the oropharyngeal cavity was analyzed to investigate possible alterations in these structures. At 42 days, samples of wood shavings were collected to determine the moisture content. The data was submitted to ANOVA and, when significant, compared using Dunnett’s test at 5%. Birds in the P100 group had better FCR (P<0.05) than birds in the M100 from 36 to 42 and 28 to 42 days. Birds fed the P100 and P34 diets had lower MS AID (P<0.05), while birds in the M100 had better CP AID compared to those fed diets with some processing (P<0.05). The treatments P66 and P34 had lower IDE than the control diet (P<0.05). In conclusion, birds fed P100 performed better, while birds fed M100 had better AID.